Global survey of star clusters in the Milky Way I: the pipeline and fundamental parameters in the second quadrant - Kharchenko, Nina V.; Schilbach, Elena; Röser, Siegfried (Astronomy and astrophysics, 2012)
Aims. On the basis of the PPMXL star catalogue we performed a survey of star clusters in the second quadrant of the Milky Way.Methods. From the PPMXL catalogue of positions and proper motions we took the subset of stars with near-infrared photometry from 2MASS and added the remaining 2MASS stars without proper motions (called 2MAst, i.e. 2MASS with astrometry). We developed a data-processing pipeline including interactive human control of a standardised set of multi-dimensional diagrams to determine kinematic and photometric membership probabilities for stars in a cluster region. The pipeline simultaneously produced the astrophysical parameters of a cluster. From literature we compiled a target list of presently known open and globular clusters, cluster candidates, associations, and moving groups. From established member stars we derived spatial parameters (coordinates of centres and radii of the main morphological parts of clusters) and cluster kinematics (average proper motions and sometimes radial velocities). For distance, reddening, and age determination we used specific sets of theoretical isochrones. Tidal parameters were obtained by a fit of three-parameter King profiles to the observed density distributions of members.Results. We investigated all 871 objects in the 2nd Galactic quadrant, of which we successfully treated 642 open clusters, 2 globular clusters, and 8 stellar associations. The remaining 219 objects (24%) were recognised by us to be nonexistent clusters, duplicate entries, or clusters too faint for 2MAst. We found that our sample is complete in the 2nd quadrant up to a distance of 2 kpc, where the average surface density is 94 clusters per kpc2. Compared with literature values we found good agreement in spatial and kinematic data, as well as for optical distances and reddening. Small, but systematic offsets were detected in the age determination.